2011
DOI: 10.1128/aem.05601-11
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of N -Acetyl- d -Neuraminic Acid from N -Acetyl- d -Glucosamine by Using the Spore Surface-Displayed N -Acetyl- d -Neuraminic Acid Aldolase

Abstract: Chemoenzymatic synthesis ofN-acetyl-d-neuraminic acid fromN-acetyl-d-glucosamine using the spore surface-displayedN-acetyl-d-neuraminic acid aldolase at a high concentration (53.9 g liter−1) was achieved in this study. Thus, displaying a target enzyme on the surface of spores might be an alternative for integration of biocatalytic conversion into chemical synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…NeuAc production by the GRAS B. subtilis strain developed in this study should be more favorable for the production of food‐grade NeuAc. Furthermore, the production method developed in this study was more economically competitive compared to the production of NeuAc by B. subtilis spores with NanA displayed on the spore surface requiring GlcNAc or ManNAc as substrates as well as complex cell disruption and spore isolation methods . Our study demonstrated that the whole‐cell biocatalysis by B. subtilis is a promising method for the production of food‐grade NeuAc.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…NeuAc production by the GRAS B. subtilis strain developed in this study should be more favorable for the production of food‐grade NeuAc. Furthermore, the production method developed in this study was more economically competitive compared to the production of NeuAc by B. subtilis spores with NanA displayed on the spore surface requiring GlcNAc or ManNAc as substrates as well as complex cell disruption and spore isolation methods . Our study demonstrated that the whole‐cell biocatalysis by B. subtilis is a promising method for the production of food‐grade NeuAc.…”
Section: Discussionmentioning
confidence: 84%
“…However, the NeuAc produced by engineered E. coli can be potentially contaminated by endotoxins, which may limit its application as a nutraceutical and a diet supplement . Therefore, NeuAc aldolase was displayed on the surface of Bacillus subtilis ( B. subtilis ) spores via a spore surface display system for the bioconversion of GlcNAc or ManNAc in combination with pyruvate to NeuAc . However, using ManNAc as a substrate and spore purification significantly increased the cost and complexity of NeuAc production, which reduced the economic feasibility for large‐scale NeuAc production.…”
Section: Introductionmentioning
confidence: 99%
“… Biocatalyst Strategy Production Applications Ref. Spore based biocatalysts Spore surface display Spore coat protein Target genes N-acetyl- d -neuraminic acid Aldolase CotG nanA 4.9 g/L/h N-acetyl- d -neuraminic acid Pharmaceutical [ 97 ] β-galactosidase CotX bgaB 8.8 g/L lactulose from 200 g/L lactose and 100 g/L of fructose Pharmaceutical and dairy industry [ 98 ] CotG araA 4.3 g/L/h d -tagatose Food industry [ 99 ] CotG lacZ 8.1 g/L octyl- d -galactopyranoside Chemical industry [ 23 , 95 ] d -psicose 3-epimerase CotG Dpe 85 g/L d -allulose from 500 g/L d -fructose Pharmaceutical and food industry [ 100 ] Haloalkane Dehydrgenase CotG dhaA 1.74 ± 0.06 U/mL hydrolyzing activitiy of haloalkane dehalogenase Bioremediation [ ...…”
Section: Engineered B Subtilis Biofilms and Spores For Biocatalysismentioning
confidence: 99%
“…The biosurfactants display better performance in biotechnology applications and have less impact on the environment than conventional surfactants, due to their higher biodegradability and lower toxicity [ 21 ]. In addition, the surface display technology has demonstrated that bioactive molecules are present on the spore surface [ 22 ]. These recombinant spores have been used for enzyme immobilization that can occur irrespective of the cytoplasmic membrane permeability barrier [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of α-D-glucosamine-1phosphate to N-acetyl-α-D-glucosamine-6-phosphate has been completed, and with phosphatases-catalyst to establish conversion of 6-ester. This reaction's key step is the rate limitation imposed by the chemical cleavage of phosphate and transfer within a molecule [33].…”
Section: The Enzymatic Modification Of N-acetyl-α-d-glucosamine-n-phosphatementioning
confidence: 99%